Pendidikan Kesehatan Dalam Pengembangan Pengetahuan Lansia Tentang Hipertensi Di Desa Tangkil Sukahati - K, Hairuddin; Yulis, Dian Meiliani; Ilham, Radiah; Noviar, Rizki Andita; Vandika, Arnes Yuli; Ariyanti, Sri (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal, resulting in an increase in morbidity and mortality rates, systolic blood pressure of 140 mmHg indicates the phase of blood being pumped by the heart and diastolic phase of 90 mmHg indicates the phase of blood returning to the heart. The purpose of PkM is to obtain a general picture and identify the level of knowledge of the elderly about hypertension. The method used in PkM activities is health education in developing the knowledge of the elderly about hypertension. The results of community service are that there are still many elderly who lack knowledge about hypertension, amounting to 21 elderly (58.34%) and good knowledge, amounting to 15 elderly (41.66%). The conclusion of this activity is the importance of increasing knowledge about hypertension for the elderly in improving the health of the elderly. Support from both family and health workers is very much needed.